2004
DOI: 10.1136/hrt.2003.018051
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in plasma concentrations of N terminal pro B type natriuretic peptide following percutaneous coronary intervention

Abstract: Btype natriuretic peptide (BNP) and its pro-peptide N terminal fragment (NTproBNP) are raised in conditions associated with abnormal ventricular structure and function and are independent predictors of survival in diverse clinical settings. Patients without raised baseline plasma BNP demonstrate an early, transient increase in concentrations following percutaneous coronary intervention (PCI), 1 but longer term effects are unknown. Potential benefits of PCI on ventricular remodelling are likely to be greatest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Post-PCI BNP levels behaved as an independent predictor of MACEs over the subsequent 12 months of follow up [22]. Interestingly, additional studies described a drop of NT-proBNP levels following either PCI or surgical revascularization, although no prognostic implications were explored in that context [23].…”
Section: Discussionmentioning
confidence: 94%
“…Post-PCI BNP levels behaved as an independent predictor of MACEs over the subsequent 12 months of follow up [22]. Interestingly, additional studies described a drop of NT-proBNP levels following either PCI or surgical revascularization, although no prognostic implications were explored in that context [23].…”
Section: Discussionmentioning
confidence: 94%
“…They demonstrated a significant decrease in plasma proBNP levels at 24 h post-intervention compared to baseline levels. They speculated that the potential reasons for decrease in proBNP level may be due to decrease in ischemic burden or changes in LV function [ 27 ]. McClure et al studied proBNP levels in 26 patients with LAD stenosis and normal baseline LV function undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of percutaneous coronary intervention also support this idea, since BNP increases transiently during balloon inflation (when ischaemia occurs), and later falls when the ischaemia is resolved. 31,32 Furthermore, a recent study by McClure et al 33 in patients with stable angina demonstrated a reduction in N-BNP concentration when measured 8 weeks following percutaneous coronary revascularisation of LAD stenosis.…”
Section: Cad and Myocardial Ischaemiamentioning
confidence: 98%